জীবন যৌবন - রায়, অন্নদাশংকর, ১৯০৪-২০০২. (কলকাতা : আনন্দ পাবলিশার্স, 1999)
Autobiographical memoirs by a 20th century Bengali author.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Rāẏa, Annadāśaṅkara, -- 1904-2002.; Authors, Bengali -- 20th century -- Biography